2021
DOI: 10.1002/mgg3.1838
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of combined methylmalonic acidemia and homocystinuria cobalamin C type using clinical exome sequencing and targeted gene analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The mother delivered a healthy baby, and the neonate did not show symptoms or signs of combined methylmalonic acidemia and homocystinuria after birth. 14 In Taiwan, a nationwide newborn screening program for isolated methylmalonic acidemia (MMA)/propionic acidemia (PA) in neonatal has shown that patients with MMA mutase type and PA cases are at risk for death and neurodevelopmental disability. The study found that MMA patients have higher AST, ALT, and NH3 values, and lower pH values.…”
Section: Discussionmentioning
confidence: 99%
“…The mother delivered a healthy baby, and the neonate did not show symptoms or signs of combined methylmalonic acidemia and homocystinuria after birth. 14 In Taiwan, a nationwide newborn screening program for isolated methylmalonic acidemia (MMA)/propionic acidemia (PA) in neonatal has shown that patients with MMA mutase type and PA cases are at risk for death and neurodevelopmental disability. The study found that MMA patients have higher AST, ALT, and NH3 values, and lower pH values.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the biochemical diagnosis, guide management, and provide genetic counseling to families, the underlying genetic defect must be identified ( Forny et al, 2021 ). MMA is highly genetically heterogeneous, and at least 10 disease-related genes have been identified; among them, mutations in MUT (mut type), MMAA (cblA type), MMAB (cblB type), MMACHC (cblC type), MMADHC (cblD type), LMBRD1 (cblF type), ABCD4 (cblJ type), and HCFC1 (cblX type) are the most common ( Hwang et al, 2021 ).…”
Section: Diagnosis Of Mmamentioning
confidence: 99%
“…A clinical cohort study reported that 12 children with cblC defects diagnosed by newborn screening were found to have developmental delays, most of whom presented with hypotonia and nystagmus, while neurodevelopmental assessments suggested that impaired motor development was the most prominent deficiency ( Weisfeld-Adams et al, 2013 ). Late-onset patients may have atypical symptoms such as mental symptoms and cognitive decline ( Hwang et al, 2021 ).…”
Section: Mechanism Of Nervous System Injury and Neurodevelopmental Ch...mentioning
confidence: 99%
“…ABCD4 is found in lysosomes and participates in the transport of cobalamin (vitamin B12) from lysosomes into the cytosol. It is linked to methylmalonic aciduria and homocystinuria type cblJ (Hwang et al, 2021 ) and is also X-linked to adrenoleukodystrophy (Kawaguchi and Imanaka, 2022 ).…”
Section: Introductionmentioning
confidence: 99%